2007
DOI: 10.1007/s11998-007-9001-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of silver nanocomposite textile

Abstract: Nanostructured silver films of different thicknesses were deposited on surfaces of polypropylene nonwovens by magnetron sputter coating to obtain antibacterial and electrical conductive properties. The surface morphology of nanostructured silver films was investigated by atomic force microscopy (AFM). The antibacterial properties of the nonwovens coated with relatively thinner films were evaluated using the shake flask test. The conductivity of the nonwovens coated with relatively thicker films was examined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 7 publications
0
42
0
Order By: Relevance
“…High bacterial growth as indicated by bacterial growth lawn (large indistinguishable collection of colonies) was observed everywhere. The observed zone of inhibition is a result of the leaching of active biocidal species Ag + ion from the embedded Ag particles present in the fabric 17 . The presence of the inhibition zone clearly indicates that the mechanism of the biocidal action of the fabric is due to the leached Ag + ion.…”
Section: Disk Diffusion Methodsmentioning
confidence: 99%
“…High bacterial growth as indicated by bacterial growth lawn (large indistinguishable collection of colonies) was observed everywhere. The observed zone of inhibition is a result of the leaching of active biocidal species Ag + ion from the embedded Ag particles present in the fabric 17 . The presence of the inhibition zone clearly indicates that the mechanism of the biocidal action of the fabric is due to the leached Ag + ion.…”
Section: Disk Diffusion Methodsmentioning
confidence: 99%
“…Several studies showed metal, that is, silver, sputtering onto polypropylene and polyester nonwovens and polyacrylonitrile electrospun nonwovens to impart antibacterial property [51,52,53]. Shahidi et al [16] deposited copper onto the surface of cotton fabric samples by DC magnetron sputtering for antibacterial effect and found that duration of the application process was shorter compared to conventional application processes using nonionic detergent and metallic salts.…”
Section: Plasma Coating Of Nonwovens For Functional and Bioactive Coamentioning
confidence: 99%
“…The surface resistance of nonwoven material was also reduced [35]. Wang et al, Sonehara et al and Jianfeng et al [36,37,38,39] reported sputtering of several metals onto polypropylene, polyester nonwovens and polyacrylonitrile electrospun nonwovens, and their results showed improved antibacterial performance and electromagnetic interference (EMI) shielding efficiency.…”
Section: Tekstil Ve Mühendismentioning
confidence: 99%